Effects of plant availability on population size and dynamics of an insect community: diamondback moth and two of its parasitoids. Issue 4 (August 2014) - Soufbaf, M.; Fathipour, Y.; Karimzadeh, J.; Zalucki, M.P.
Abstract To understand the effect of plant availability/structure on the population size and dynamics of insects, a specialist herbivore in the presence of two of its parasitoids was studied in four replicated time-series experiments with high and low plant availabilities; under the latter condition, the herbivore suffered from some periods of resource limitation (starvation) and little plant-related structural refuges. Population dynamics of the parasitoid Cotesia vestalis was governed mainly by the delayed density-dependent process under both plant setups. The parasitoid, Diadegma semiclausum, under different plant availabilities and different coexistence situations (either +competitor or –competitor) showed dynamics patterns that were governed mainly by the delayed density process (significant lags at weeks 2–4). Both the competing parasitoids did not experience beneficial or costly interferences from each other in terms of their own population size when the plant resource was limited. Variation in the Plutella xylostella population under limited plant availability is higher than that under the other plant setup. For both parasitoids, under limited plant setup, the extinction risk was lower when parasitoids were engaged in competition, while under the unlimited plant setup, the mentioned risk was higher when parasitoids competed. In this situation, parasitoids suffered from two forces, competition and higher escaped hosts.